Letting Go: Conceptualizing Intervention De‐implementation in Public Health and Social Service Settings. Issue 1 (3rd July 2018) - McKay, Virginia R.; Morshed, Alexandra B.; Brownson, Ross C.; Proctor, Enola K.; Prusaczyk, Beth
Highlights: Thinking through when to let go: theory for identifying interventions that may not add value. Examples of interventions ideal for discontinuation in public health and social service settings. De‐implementation of interventions in the context of dissemination and implementation science. Abstract: The discontinuation of interventions that should be stopped, or de‐implementation, has emerged as a novel line of inquiry within dissemination and implementation science. As this area grows in human services research, like public health and social work, theory is needed to help guide scientific endeavors. Given the infancy of de‐implementation, this conceptual narrative provides a definition and criteria for determining if an intervention should be de‐implemented. We identify three criteria for identifying interventions appropriate for de‐implementation: (a) interventions that are not effective or harmful, (b) interventions that are not the most effective or efficient to provide, and (c) interventions that are no longer necessary. Detailed, well‐documented examples illustrate each of the criteria. We describe de‐implementation frameworks, but also demonstrate how other existing implementation frameworks might be applied to de‐implementation research as a supplement. Finally, we conclude with a discussion of de‐implementation in the context of other stages of implementation, like sustainability and adoption; next steps for de‐implementation research, especially identifying interventions appropriate for de‐implementation in a systematic manner; and highlight special ethical considerations to advance the field of de‐implementation research.